Evaluating the spatial suitability of primary schools for boys in the city of Makkah using multi-criteria geographic information systems - Yamani, Abdullah AbdulAziz; Al-Salmi, Morshed Muayoud (Journal of Humanities & Social Sciences, 2025)
The research aims to model suitability of Makkah city for primary schools for boys and evaluate suitability of locations of these schools. The research adopted on modeling fifteen spatial variables, six of which within natural environment risks such as slope, water and air pollution. Nine of them within feasibility variable such  population density, accessibility such distance from housing and roads, and human environment risks such distance from roads, power lines, fuel and energy stations, factories and gas sales centers. the research methodology Gradient from collecting school data and criteria determine the most suitable areas for schools in the city. This data was processed in preparation for deriving maps showing the suitability of each criterion, and the suitability of schools for each was evaluated, arriving to determining the relative importance of model criteria using Analytical Hierarchy Process (AHP), followed by use of Multiple-criteria decision analysis (MCDA) to merge criteria layers of criteria according their relative importance, using Raster Calculator in geographic information systems, to obtain a map showing suitability city of Makkah Al Mukarramah for schools according to various criteria. Accordingly, results of this research showed that suitability Makkah city for primary schools for boys ranged between 45.6% south, southwest and north of Makkah city, to 97.2% in areas most suitable for schools north, northeast, southeast and central west of Makkah city, with a spatial average suitability rate at city level 76.8%. the results of the evaluation of suitability of primary schools for boys in Makkah city concentration of 104 schools by 65.83% of their total number, in areas with moderate suitability 70 - 80%, and about 43 primary schools by 27.22% of total primary schools for boys, with a rate ranging 80 - 90% in areas with high suitability.
Keywords: Spatial suitability; Schools; Makkah; GIS